Photoproducts of Porphyrins with a Focus on Protoporphyrin IX - Simone König (Photochem, 2025)
Porphyrins play important roles in biological systems including oxygen transport and catalysis. Due to their tetrapyrrole core structure, they exhibit exceptional photophysical and electrochemical properties and find many applications in both technical and life science fields, including photodynamic therapy and neurosurgery. The irradiation of porphyrins may cause modifications to their molecular structure or their degradation. Such photobleaching processes potentially affect the success and sensitivity of photosensitizer applications. While there have been many studies using fluorescence spectroscopy to investigate this phenomenon, reports about analytically validated structures of photoproducts are scarce. It is, however, necessary to know the individual contributions of different molecules to the fluorescence signal in order to evaluate it correctly. This review provides a summary of the current state of knowledge in this respect, discussing especially the validated hydroxyaldehyde and formyl photo-oxidation products of protoporphyrin IX.